Determinación de estándares para la acreditación de servicios odontológicos y su aplicación en la clínica odontológica de la U.N.M.S.M.. 2001 - Molina Albomoz, Vladimiro Germán (2002)
OBJECTIVE: To establish the necessary minimum standards so that a dentistry clinical university student fulfills its assistance educational function . To evaluate the Dentistry Clinical and to elaborate a proposal of minimum standards. METHODOLOGY: You applies the qualitative method of action participation. The data were gathered through the participant observation and the interviews to the odontologyst, educational of the university and experts of other institutions. RESULTS: The standards to evaluate a dentistry clinical were carried out keeping in mind, the following components: a component A, referred to the administration documents for the processes of attention, and a component B, referred to the infrastructure that he will understand the minimum conditions as for Atmospheres, teams and facilities where they are carried out the attentions odontologicas.